Learning Organization and its Cultural Manifestations: Evidence from a Global White Goods Manufacturer - GÜRBÜZ, FATMA GÜLRUH (ELSEVIER SCIENCE BV, 2015)
Being a leader is critical and difficult to sustain in today's highly competitive business world. In present study, a leader company in white goods sector is examined to explore its core cultural competency. The critical characteristic of the company is found as its being a learning organization. Various cultural manifestations of the company are analyzed according to Senge's five disciplines. Exploratory case study technique is used in order to understand a complex phenomenon of being a learning organization.
Keywords: Learning organization; organizational culture; artifacts; espoused values; case study